Fatigue in chronic cholestasis. Issue 4 (11th March 2004) - Milkiewicz, P; Heathcote, E J
Abstract : Fatigue is probably the most intriguing symptom affecting patients with chronic cholestatic disorders, in particular those with primary biliary cirrhosis. It is postulated that fatigue in patients with primary biliary cirrhosis may be associated with morphological abnormalities of the central nervous system secondary to accumulation of manganese. However, we are still far from understanding this complex issue.